CLEARANCE OF MYCOPLASMA GENITALIUM AND TRICHOMONAS VAGINALIS AMONG ADOLESCENTS AND YOUNG ADULTS WITH PELVIC INFLAMMATORY DISEASE: RESULTS FROM THE TECH-N STUDY - Trent, Maria (Sex Transm Dis, 2020)
Current PID treatment effectively treats Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT). However, coverage may be inadequate for Mycoplasma genitalium (MG)/Trichomonas vaginalis (TV) infections. We compared the longitudinal MG and TV outcomes with NG/CT outcomes for women enrolled in a longitudinal randomized controlled trial to optimize outcomes after PID. The prevalence of CT and NG were lower at 30 days and 90 days follow-up compared to the prevalence at time of diagnosis. No significant difference was observed for MG (OR 0.95, 0.86–1.04, p-0.265) and TV (OR 0.89, 0.75–1.04, p-0.146) over time for both treatment groups, showing that persistence and or reinfection with MG and TV occur more frequently than with CT or NG following treatment for PID using current national treatment guidelines.